2018
DOI: 10.1097/md.0000000000011124
|View full text |Cite|
|
Sign up to set email alerts
|

The outcomes and prognostic factors of the patients with unplanned intensive care unit readmissions

Abstract: This retrospective cohort study investigated the outcomes of patients with unplanned intensive care unit (ICU) readmission.All of the patients readmitted to ICU within 48 hours between 2010 and 2016 were enrolled.A total of 99 patients early readmitted to ICU were identified and their mean age of the patients was 68.8 ± 14.8 years. Respiratory failure was the most common cause of ICU readmission (n = 48, 48.5%), followed by acute myocardial ischemia or worsening heart failure (n = 25, 25.3%), sepsis (n = 22, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
3
27
1
1
Order By: Relevance
“…Particularly, hypertension has been prevalent among individuals with a mean age 44, whereas the mean age for diabetes is 49 years old [ 28 ]. Similar to other studies, we observed higher mortality among male patients (62.1%) [ 22 24 ], inpatients transferred to the ICU (18.2%), and diagnosed with sepsis (41.9%). Those findings are 2.5 times higher than those observed in multicentric studies conducted in 65 ICU from all Brazilian territory where mortality rates by sepsis alone were 16.7% [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Particularly, hypertension has been prevalent among individuals with a mean age 44, whereas the mean age for diabetes is 49 years old [ 28 ]. Similar to other studies, we observed higher mortality among male patients (62.1%) [ 22 24 ], inpatients transferred to the ICU (18.2%), and diagnosed with sepsis (41.9%). Those findings are 2.5 times higher than those observed in multicentric studies conducted in 65 ICU from all Brazilian territory where mortality rates by sepsis alone were 16.7% [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…is study identified a 21% ICU mortality rate among patients in the hospital of Sergipe, northeastern Brazil. e mortality rate is considered high when compared to other national and international studies [1,2,[23][24][25]. Age, admission from inpatient unit, sepsis, hydroelectrolyte imbalance, changes in glycemic index, tube feeding, mechanic ventilation, sedation with fentanyl, insulin use, and higher Charlson scores were associated with mortality in this study.…”
Section: Discussionmentioning
confidence: 55%
“…In conclusion, the patients who are discharged from ICU are at a high risk of being readmitted to ICU (34). Readmission to ICU is associated with higher mortality risk than the initial admission (35). Considering the funding for ICU services which consumes substantial amount of health resources, a decrease in the readmission to ICU rates can be used as a hospital performance indicator (36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…Organ dysfunction can be identified as an acute change in the total SOFA score of 2 points consequent to infection (13). Respiratory failure was the most common cause of intensive care unit (ICU) admission, followed by acute myocardial ischemia or worsening heart failure, sepsis, gastrointestinal disease, and neurological disease (14). Patients who underwent emergency surgery for peritonitis due to colorectal perforation, did not develop respiratory disorders and required short-term mechanical ventilation after surgery, did not develop sepsis.…”
Section: Discussionmentioning
confidence: 99%